2009
DOI: 10.1021/jp902417j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of C60 on the Photocatalytic Activity of TiO2 Nanorods

Abstract: C 60 -incorporated TiO 2 nanorods were prepared in a hydrothermal process. Rhodamine B (RhB) as a model pollutant was used to probe the photocatalytic activity of products. The results showed that the photocatalytic activity of TiO 2 nanorods incorporated with C 60 under visible light irradiation markedly increased by a factor of approximately 3.3 when compared with pure TiO 2 nanorods and approximately 2.7 when compared with Degussa P25, respectively. The enhanced photocatalytic activity under visible light i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…In recent years, many studies have been reported involving the use of TiO 2 -based photocatalyst due to the physical and chemical stability, low cost, non-toxicity and unique electronic and optical properties of titania [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have been reported involving the use of TiO 2 -based photocatalyst due to the physical and chemical stability, low cost, non-toxicity and unique electronic and optical properties of titania [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The result indicates that Au nanoparticles supported on ZnO nanowires enhance the photocatalytic ability of ZnO nanowires for benzene degradation. On the basis of previous studies, the most reasonable rationalization, which is similar to that in the C 60 /ZnO (or TiO 2 ) composites photocatalysis [30,37,38], is shown in Scheme 2. In the first step, in this case, ZnO nanowires were excited by UV light with larger energy than the bandgap (3.37 eV) of ZnO leading to the generation of electrons in the semiconductor conduction band and holes in valence band.…”
Section: Uv Light Photodegradation Benzenementioning
confidence: 83%
“…Long et al [39] synthesized C 60 nanoparticles incorporated TiO 2 nanorods. The photocatalytic activity of C 60 /TiO 2 nanorods is about 3.3 times higher than that of TiO 2 nanorods.…”
Section: D/1dmentioning
confidence: 99%